Amelioration in Indonesian Classics: A Corpus Analysis of Concrete Nouns in Indonesian Literary Works - Lubis, Nurhabibah; Ermanto, Ermanto (Journal of Languages and Language Teaching, 2025)
This research analyzes the phenomenon of amelioration on concrete nouns in the novels Layar Terkembang by Sutan Takdir Alisjahbana and Sitti Nurbaya by Marah Roesli. Amelioration is the process of changing the meaning of a word that leads to a more positive connotation. The purpose of this study is to identify the forms of amelioration, the positive connotations formed, and how these changes in meaning reflect the social and cultural context of colonial Indonesia. The research method used is corpus linguistics with documentation techniques through the KORTARA (Korpus Nusantara) application to identify frequency patterns and word collocation in literary texts. The results showed that there were 57 words undergoing amelioration that reflected changes in social views, culture, and religious values. For example, the word "khalikulalam" in Sitti Nurbaya's novel has undergone improvements, a shift in meaning that increases its value and respect; The word "virgin" in the novel Layar Terkembang carries a more subtle and respectful connotation, describing a young woman who is seen not only by her status but also associated with beauty, purity. The words not only have basic meanings, but also additional connotations that symbolize respect, sanctity, spiritual power, and cultural pride. The amelioration of these concrete nouns shows the changes in colonial society's perspective towards social roles and cultural values in daily life. The findings support the theory that amelioration is closely related to broader social dynamics, where words with high moral and cultural values tend to experience an increase in meaning. This research is expected to contribute to the study of Indonesian linguistics and semantic education, as well as add to the understanding of the interaction between language and social values in society.